Urine Output in Males and Females after Lasix consumption - Jabir, Sara (faculty of applied basic medical science - Libyan international medical university, 2022)
FUR is a well-known chemical anion that works as a diuretic by inhibiting ion transport by binding to the Na-K-2Cl cotransporter (NKCC2) in the thick ascending limb (TAL) resulting in excessive excretion of water along with sodium, chloride, magnesium, and calcium. FUR is a drug that is often used to treat edema, congestive heart failure, liver cirrhosis, and nephrotic syndrome. Gender has been associated to variations in drug disposition and therapeutic agent response. In male and female house mice a series of five experiments were utilized to test hypotheses concerning variables impacting excreted urine production per day. Urine was collected for twenty-four hours in metabolism cages. Male house mice discharge urine 1.5–2.0 times more frequently than females. For both sexes and mice of the identical age, daily average urine production increases with age; urine output per day is related to body mass. In six male and six female normal volunteers, the diuretic response to oral hydrochlorothiazide, oral and intravenous furosemide was assessed on four successive days, each participant received single doses of the various diuretics or no therapy after fasting overnight. Over the next 24 hours, total urine production was collected for volume measurement and sodium and potassium content testing. Between the treatments, there was no statistically significant change in urine flow rate, sodium, or potassium excretion rates between male and female individuals
Keywords: Lasix